Online adaptive radiotherapy for head and neck cancers on the MR linear Accelerator: Introducing a novel modified Adapt-to-Shape approach. (January 2022) - Gupta, Amit; Dunlop, Alex; Mitchell, Adam; McQuaid, Dualta; Nill, Simeon; Barnes, Helen; Newbold, Kate; Nutting, Chris; Bhide, Shreerang; Oelfke, Uwe; Harrington, Kevin Joseph; Wong, Kee Howe
Highlights: The MR-Linac provides the tools to deliver online MR-guided Adaptive Radiotherapy Adapt-to-Shape-Lite is a novel radiotherapy planning workflow on the Elekta Unity MR-Linac Adapt-to-Shape-Lite generated plans that fulfilled 99.9% of mandatory dose constraints Adapt-to-Shape-Lite workflow can generate plans in relatively short durations Therefore, we prefer Adapt-To-Shape-Lite as the primary workflow to treat Head-and-Neck cancers Abstract: Introduction: The Elekta Unity MR-Linac (MRL) has enabled adaptive radiotherapy (ART) for patients with head and neck cancers (HNC). Adapt-To-Shape-Lite (ATS-Lite) is a novel Adapt-to-Shape strategy that provides ART without requiring daily clinician presence to perform online target and organ at risk (OAR) delineation. In this study we compared the performance of our clinically-delivered ATS-Lite strategy against three Adapt-To-Position (ATP) variants: Adapt Segments (ATP-AS), Optimise Weights (ATP-OW), and Optimise Shapes (ATP-OS). Methods: Two patients with HNC received radical-dose radiotherapy on the MRL. For each fraction, an ATS-Lite plan was generated online and delivered and additional plans were generated offline for each ATP variant. To assess the clinical acceptability of a plan for every fraction, twenty clinical goals for targets and OARs were assessed for all four plans. Results: 53 fractions were analysed. ATS-Lite passed 99.9% of mandatory dose constraints. ATP-AS and ATP-OW each failed 7.6% of mandatory dose constraints. The Planning Target Volumes for 54 Gy (D95% and D98%) were the most frequently failing dose constraint targets for ATP. ATS-Lite median fraction times for Patient 1 and 2 were 40 mins 9 s (range 28 mins 16 s – 47 mins 20 s) and 32 mins 14 s (range 25 mins 33 s – 44 mins 27 s), respectively. Conclusions: Our early data show that the novel ATS-Lite strategy produced plans that fulfilled 99.9% of clinical dose constraints in a time frame that is tolerable for patients and comparable to ATP workflows. Therefore, ATS-Lite, which bridges the gap between ATP and full ATS, will be further utilised and developed within our institute and it is a workflow that should be considered for treating patients with HNC on the MRL.